Pengaruh Insentif Dan Motivasi Terhadap Kinerja Karyawan Pada PT Sentral Koneksi Internasional - Ngono Citra Zippora; Harsono Teguh S; Achmad Daengs GS; Sugiharto Sugiharto; Bambang Karnain P (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine how much influence incentives and motivation have on employee performance at PT Sentral Kontak Internasional. Human resources have a very important role for the company to achieve the set targets. PT Sentral Kontak Internasional provides incentives as a trigger to increase motivation on employee performance. This type of research is quantitative, this study uses the entire population / saturated sample, namely as many as 50 respondents. Of the 50 respondents, 32 were male and 18 were female. The sampling technique for this study used a questionnaire with a sample of 50 people. This study used multiple linear regression testing with the SPSS 26 data processing application. The results showed that the incentive variable had a partial effect on employee performance with the result t calculated on the incentive variable (X1) showing the number 2.614. The calculated t value is greater than t table or 2.614 > 2.011. Motivation has a partial effect on Employee Performance at PT Sentral Kontak Internasional with the t-count on the Motivation variable (X2) showing the number 11.819. The calculated t value is greater than t table or 11.819 > 2.011. Then motivation (X2) has a partial effect on employee performance. The results of the F test count the simultaneous test of Incentives (X1) and Motivation (X2) on Employee Performance (Y) with a result of 84.284. The calculated F value is greater than the F table or 84.284 > 3.20. It can be concluded that incentives (X1) and motivation (X2) have a significant effect on employee performance (Y) simultaneously.